PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI POLA GAMBAR DAN POLA BILANGAN DI KELAS IV SEKOLAH DASAR - Lidya Febryanti; Syafri Ahmad (STKIP Subang, 2024)
This study aims to describe how to improve the learning outcomes of students on the material of image patterns and number patterns using the Problem Based Learning (PBL) model in class IV Elementary School. The research method used is Classroom Action Research using quantitative and qualitative approaches. The subject of this research involved 20 fourth grade elementary school students. The results of this study showed that: The results showed that: First, the teaching module of cycle I obtained an average of 87.5% (B), increased in cycle II to 95.8% (SB). Second, the results of the implementation of learning aspects of the teacher of cycle I obtained an average of 85.71% (B), increased in cycle II to 96.42% (SB). Third, the results of the implementation of learning aspects of students in cycle I obtained an average of 82.14% (B), increasing in cycle II to 92.85% (SB). Fourth, the learning outcomes of students in cycle I obtained an average of 74.8 (C), increasing in cycle II to 91.88 (SB). Thus, it can be concluded that the Problem Based Learning (PBL) model can improve the learning outcomes of students in learning Picture Patterns and Number Patterns in class IV Elementary School.